Recombinant adeno-associated virus (rAAV)-mediated expression of a human gamma-globin gene in human progenitor-derived erythroid cells. - Miller, J L (1994)
Effective gene therapy for the severe hemoglobin (Hb) disorders, sickle-cell anemia and thalassemia, will require an efficient method to transfer, integrate, and express a globin gene in primary erythroid cells. To evaluate recombinant adeno-associated virus (rAAV) for this purpose, we constructed a rAAV vector encoding a human gamma-globin gene (pJM24/vHS432A gamma). Its 4725-nucleotide genome consists of two 180-bp AAV inverted terminal repeats flanking the core elements of hypersensitive sites 2, 3, and 4 from the locus control region of the beta-globin gene cluster, linked to a mutationally marked A gamma-globin gene (A gamma) containing native promoter and RNA processing signals. CD34+ human hematopoietic cells were exposed to rAAV particles at a multiplicity of infection of 500-1000 and cultured in semisolid medium containing several cytokines. A reverse transcriptase polymerase chain reaction assay distinguished mRNA signals derived from transduced and endogenous human gamma-globin genes. Twenty to 40% of human erythroid burst-forming unit-derived colonies expressed the rAAV-transduced A gamma-globin gene at levels 4-71% that of the endogenous gamma-globin genes. The HbF content of pooled control colonies was 26%, whereas HbF was 40% of the total in pooled colonies derived from rAAV transduced progenitors. These data establish that rAAV containing elements from the locus control region linked to a gamma-globin gene are capable of transferring and expressing that gene in primary human hematopoietic cells resulting in a substantial increase in HbF content.